2022
DOI: 10.1002/mgg3.2009
|View full text |Cite
|
Sign up to set email alerts
|

Ten‐year follow‐up of Nicolaides–Baraitser syndrome with a de novo mutation and analysis of 58 gene loci of SMARCA2‐associated NCBRS

Abstract: As a clinical subtype of SWI/SNF‐related intellectual disability syndromes, Nicolaides–Baraitser syndrome (NCBRS, OMIM601358) has a unique genotype–phenotype. Due to the scarcity of the number of cases reported and the limitations of diagnosis methods, so far only more than 80 cases have been reported worldwide. In this article, a new patient with a de novo mutation was followed up for 10 years; it includes the epilepsy treatment process, the characteristics of NBCRS with seizures, typical faces, sparse hair, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Additional variants that were excluded for further analyses included: (1) RHNO1 c.250C>T; p.Arg84Ter in the index OC case (PT0158) from family F1288; (2) ATRX c.4377_4379del; p.Glu1464del in one of the index OC case (PT0057) from family F1528 as they were classified as benign in ClinVar and by ACMG guidelines, and the latter as not being harboured by the other index OC case of the same family F1528 ( Figure S1 ); (3) SMARCA2 c.3265C>T in the index OC case (PT0128) from family F694; p.Arg1089Trp; and (4) KMT2C c.6916C>T; p.Pro2306Ser in the index OC case (PT0047) from family F1490 as variants in these genes are associated with non-cancer related syndromes ( Figure S1 ). Heterozygous germline variants in SMARCA2 are linked with Nicolaides-Baraitser syndrome (MIM: 601358), which is characterized by intellectual disability, seizures, limited to absence of speech ability, short stature, dysmorphic facial features and sparse hair ( 91 , 92 ; 93 97 ); and heterozygous germline variants in KMT2C are linked with Kleefstra syndrome, type 2 (MIM: 617768), which is characterized by delayed psychomotor development, variable intellectual disability and mild dysmorphic features ( 98 101 ). A genotype-phenotype of heterozygous variants located within exon 15-25 of SMARCA2 , which encodes the ATPase domain, have been recently reported that over 80% of these variants were de novo based on WES analyses of 80 cases in trios with Nicolaides-Baraitser syndrome that have been documented worldwide so far ( 92 , 95 , 97 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Additional variants that were excluded for further analyses included: (1) RHNO1 c.250C>T; p.Arg84Ter in the index OC case (PT0158) from family F1288; (2) ATRX c.4377_4379del; p.Glu1464del in one of the index OC case (PT0057) from family F1528 as they were classified as benign in ClinVar and by ACMG guidelines, and the latter as not being harboured by the other index OC case of the same family F1528 ( Figure S1 ); (3) SMARCA2 c.3265C>T in the index OC case (PT0128) from family F694; p.Arg1089Trp; and (4) KMT2C c.6916C>T; p.Pro2306Ser in the index OC case (PT0047) from family F1490 as variants in these genes are associated with non-cancer related syndromes ( Figure S1 ). Heterozygous germline variants in SMARCA2 are linked with Nicolaides-Baraitser syndrome (MIM: 601358), which is characterized by intellectual disability, seizures, limited to absence of speech ability, short stature, dysmorphic facial features and sparse hair ( 91 , 92 ; 93 97 ); and heterozygous germline variants in KMT2C are linked with Kleefstra syndrome, type 2 (MIM: 617768), which is characterized by delayed psychomotor development, variable intellectual disability and mild dysmorphic features ( 98 101 ). A genotype-phenotype of heterozygous variants located within exon 15-25 of SMARCA2 , which encodes the ATPase domain, have been recently reported that over 80% of these variants were de novo based on WES analyses of 80 cases in trios with Nicolaides-Baraitser syndrome that have been documented worldwide so far ( 92 , 95 , 97 ).…”
Section: Resultsmentioning
confidence: 99%
“…Heterozygous germline variants in SMARCA2 are linked with Nicolaides-Baraitser syndrome (MIM: 601358), which is characterized by intellectual disability, seizures, limited to absence of speech ability, short stature, dysmorphic facial features and sparse hair ( 91 , 92 ; 93 97 ); and heterozygous germline variants in KMT2C are linked with Kleefstra syndrome, type 2 (MIM: 617768), which is characterized by delayed psychomotor development, variable intellectual disability and mild dysmorphic features ( 98 101 ). A genotype-phenotype of heterozygous variants located within exon 15-25 of SMARCA2 , which encodes the ATPase domain, have been recently reported that over 80% of these variants were de novo based on WES analyses of 80 cases in trios with Nicolaides-Baraitser syndrome that have been documented worldwide so far ( 92 , 95 , 97 ). Our SMARCA2 c.3265C>T; p.Arg1089Trp has never been reported in the literature, but it is located in exon 23 that encodes the ATPase domain ( 97 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Nicolaides-Baraitser syndrome (NCBRS) (OMIM 601358), caused by a pathogenic mutation in the SMARCA2 gene, is an autosomal dominant disease going along with intellectual delay, facial coarsening, short stature, seizures, and prominent interphalangeal joints (Sousa et al, 2014). More than 80 individuals with NCBRS caused by a mutation in the SMARCA2 gene have been reported worldwide, and 58 were caused by DNMs (Zhang et al, 2022).…”
Section: Introductionmentioning
confidence: 99%